2016
DOI: 10.3109/13880209.2016.1151444
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities and molecular mechanisms of the ethanol extracts ofBaccharispropolis andEucalyptuspropolis in RAW64.7 cells

Abstract: Context Numerous studies have reported that propolis possesses strong antioxidant activities. However, their antioxidant molecular mechanisms are unclear. Objective We utilize ethanol extracts of Chinese propolis (EECP) as a reference to compare ethanol extracts of Eucalyptus propolis (EEEP) with ethanol extracts of Baccharis propolis (EEBGP) based on their antioxidant capacities and underlying molecular mechanisms. Materials and methods HPLC and chemical analysis are utilized to evaluate compositions and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…On the whole, these results are consistent with those obtained in different conditions by Zhang et al which showed that brown propolis exerts radical scavengering and reducing activities, and is able to induce the nuclear translocation of NFE2L2, which, in turn, can activate the translation of antioxidant genes and phase II detoxication genes, such as HO-1 and GCLM [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the whole, these results are consistent with those obtained in different conditions by Zhang et al which showed that brown propolis exerts radical scavengering and reducing activities, and is able to induce the nuclear translocation of NFE2L2, which, in turn, can activate the translation of antioxidant genes and phase II detoxication genes, such as HO-1 and GCLM [ 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…This was followed by the capacity to scavenge the DPPH radicals. These properties could be attributed to be as a result of TPC, TFC and anthocyanin which are considered as the most dominant compounds found in the rice extracts (Zhang et al, 2016;Rahman et al, 2017). Although the antioxidant capacity observed in DPPH radical scavenging assay was much lower than those of ABTS and FRAP, all assays exhibited similar trends of results.…”
Section: Effects On the Antioxidative Propertiesmentioning
confidence: 99%
“…BGP is used in traditional drugs or supplements because it has a wide range of beneficial biological activities including antibiotic, antivirus, antioxidative, and anti-inflammatory effects 2 , 3 . Previous studies have shown that EEBGP and its major ingredient, artepillin C, directly eliminate reactive oxygen species (ROS) as radical scavengers and induce the activity of antioxidative enzymes in vitro 4 , 5 , 6 . Oral administration of EEBGP prevented hepatic damage induced by α-naphthyl-isothiocyanate 7 or water immersion restraint stress in rats 8 .…”
Section: Introductionmentioning
confidence: 99%